Analysis of Corruption Criminal Punishment Based on Qawāid Fiqhiyyah - Rahmawati, Lutfia; Multazam , Umar (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
This study uses an Islamic approach with a fiqh perspective based on Qawāid Fiqhiyyah to address corruption. This means they combine subjective (based on Islamic views), primordialist (rooted in Islamic religious and cultural identity) and dogmatic (based on strictly applied Qawāid Fiqhiyyah principles) approaches to deal with the complex and dilemmatic problem of corruption. This approach allows them to treat corruption not just as a legal crime, as well as a moral and social problem that needs to be resolved by taking into account religious values ​​​​and the principles of justice and public benefit regulated in Qawāid Fiqhiyyah. In the context of Qawāid Fiqhiyyah, this approach reflects the main principles that focus on justice, community welfare and prevention of damage. Qawāid Fiqhiyyah emphasizes the importance of fair and efficient law enforcement (الضرر يزال -